RESEARCH OF PROCESSES OF FORMATION OF STRUCTURE AND THE PENO-SILIKAT-NATRIEVYH MAIN PROPERTIES OF COMPOSITIONS WITH USE OF THE DEHYDRATED SLATE CLAYS - N. K. Akaev; I. A. Gasanov; Z. A. Manturov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In this article we review the results of theoretical and experimental researches for revealing the possibility of using local dehydrated slate clay as a temperature- resistant component in the process of making of foam-silicate-sodium compositions. The influence of silicate-block’s module, dispersion and the heating temperatures of the mixture on its solubility have been studied for this purpose. Besides here there were brought the results of research work concerning the influence of the heat treatment temperature and anhydrous silicate of sodium content on shrinking processes of foam compositions with the addition of small porous filler or without it.